Spiritual Caregiving and Assessments for America’s Religious ‘Nones’: A Chaplaincy Perspective - Potts, Garrett (Journal of religion and health, 2023)
One in four American patients now identify as religiously unaffiliated. This study utilizes thematic analysis to deliver qualitative results from in-depth interviews conducted with five chaplains at a premier cancer research institution in Florida to envision what care for their spiritual dimension should look like in practice. It demonstrates why the chaplains interviewed suggested that spiritual caregiving still contributes to their holistic wellbeing, and it suggests how spiritual care and assessments may be provided to so-called religious ‘nones’—or those who identify as spiritual but not religious, not religiously affiliated, secular humanist, atheist, agnostic, and so on. We conclude with a novel spirituality assessment for use while serving this patient population.